1998
DOI: 10.1006/jmbi.1997.1590
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycoside binding to the hammerhead ribozyme: a general model for the interaction of cationic antibiotics with RNA 1 1Edited by J. Karn

Abstract: A variety of drugs inhibit biological key processes by binding to a speci®c RNA component. We focus here on the well-analysed hammerhead ribozyme RNA that is inhibited by aminoglycoside antibiotics, a process considered as a paradigm for studying drug/RNA interactions. With insight gained from molecular dynamics simulations of the ribozyme in the presence of Mg 2 identi®ed by crystallography and of aminoglycosides in solution, a general model for aminoglycoside binding to RNA is proposed. A striking structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
166
0
11

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 181 publications
(190 citation statements)
references
References 45 publications
11
166
0
11
Order By: Relevance
“…Chemically modified aminoglycosides in which amino groups had systematically been added [99] or hydroxyl groups removed one at a time [100] were analyzed for their binding and inhibitory effects on the catalytic hammerhead RNA. Binding affinities of modified aminoglycosides correlate with the number and basicity of cationic ammonium groups [61], supporting a general model for the interaction of cationic antibiotics with RNA based on structural electrostatic complementarity [60]. Similar findings were reported from screening of designed neomycin B analogs targeting the A site of eubacterial 16S rRNA [93].…”
Section: Rational Design and Combina-torial Synthesis Of Rna Binderssupporting
confidence: 73%
See 2 more Smart Citations
“…Chemically modified aminoglycosides in which amino groups had systematically been added [99] or hydroxyl groups removed one at a time [100] were analyzed for their binding and inhibitory effects on the catalytic hammerhead RNA. Binding affinities of modified aminoglycosides correlate with the number and basicity of cationic ammonium groups [61], supporting a general model for the interaction of cationic antibiotics with RNA based on structural electrostatic complementarity [60]. Similar findings were reported from screening of designed neomycin B analogs targeting the A site of eubacterial 16S rRNA [93].…”
Section: Rational Design and Combina-torial Synthesis Of Rna Binderssupporting
confidence: 73%
“…This is illustrated by the examples of thiostrepton recognition in the tertiary folded GTPase center of eubacterial 23S rRNA [56][57][58], recognition of the cyclic peptide antibiotic viomycin by RNA pseudoknots [59], and aminoglycoside binding at the three-way junction of the hammerhead ribozyme [45,60,61]. In contrast, the aminoglycoside binding site in the 16S rRNA fold is located at the A site ( Fig.…”
Section: Definition and Explorationmentioning
confidence: 99%
See 1 more Smart Citation
“…Neomycin B inhibits translation at the prokaryotic ribosome by inducing misreading of the genetic code (Davies et al+, 1965;Davies & Davis, 1968)+ Furthermore, several aminoglycosides inhibit the catalytic activity of self-splicing group I introns and of the hammerhead and HDV ribozymes in vitro (von Ahsen et al+, 1991;Stage et al+, 1995;Rogers et al+, 1996)+ Two RNA-protein interactions in HIV, RRE-Rev and TarTat, are disrupted by neomycin B in vitro (Zapp et al+, 1993;Mei et al+, 1995)+ Detailed analyses of neomycin binding sites have revealed two types of RNA target sites for aminoglycoside antibiotics+ The first type contains internal asymmetrical loops with widened major grooves, which are found in the decoding site of the 16S rRNA (Noller, 1991;Purohit & Stern, 1994;Fourmy et al+, 1996;Recht et al+, 1996), in the RRE RNA of HIV (Zapp et al+, 1993), in the P4/P5 internal loop of group I introns (von Ahsen & Noller, 1993;Cate et al+, 1996;Hoch et al+, 1998), and in several neomycin aptamers isolated via in vitro selection (Wallis et al+, 1995)+ The second type of target sites are divalent metal ion binding sites in the core of ribozymes (Clouet d'Orval et al+, 1995;Rogers et al+, 1996;Hoch et al+, 1998)+ Molecular-dynamics-simulation experiments revealed that the distances between positively charged aminogroups of aminoglycosides coincide with the distances of several divalent metal ions in the X-ray structure of the hammerhead ribozyme+ This leads to the proposal that neomycin B acts via simultaneous displacement of several essential metal ions (Hermann & Westhof, 1998)+ The inhibitory neomycin binding site in the T4 phage td intron was shown to be a type-two binding site (Hoch et al+, 1998)+ Inhibition of translation and disruption of the RRERev interaction by neomycin B has been demonstrated to occur both in vitro and in vivo (Benveniste & Davies, 1973;Zapp et al+, 1993)+ While the concentrations of neomycin B required to inhibit translation are similar in vivo and in vitro, disruption of the RRE-Rev interaction required almost 100-fold higher concentrations in vivo than in vitro+ These observations suggest that aminoglycoside binding might differ substantially depending on the intracellular conditions+ Here we examined the effects of neomycin B and several other aminoglycosides on splicing of the td intron in vivo+…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that aminoglycoside antibiotics inhibit the cleavage reaction of the ribozyme (126). Among various aminoglycosides that have been tested (such as gentamycin, kanamycin, neomycin, paramomycin, lividomycin, ribostamycin, neamine, butirosin, apramycin and streptomycin), neomycin and 5-episisomicin have been reported as the strongest inhibitors (127,128).…”
Section: Antibioticsmentioning
confidence: 99%